1990
DOI: 10.1017/s0003356100005547
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme supplementation of low or high crude protein concentration diets for broiler chickens

Abstract: Previous investigations have established that supplementing broiler chicken diets with appropriate endosperm cell wall degrading enzymes can improve nutrient digestion, and indicated that this could allow lower protein diets to be used. In this study the effect of enzyme supplementation on the productive value of low (192 g/kg dry matter (DM)) and high (227 g/kg DM) protein diets was studied. The diets employed were based on barley, wheat and rye, and the two enzyme preparations used, Glucanase GP 5000® and No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The growth performance for birds supplemented with xylanase suggests that the level of inclusion used within this study was not beneficial. Pettersson et al (1990) observed similar lack of growth response associated with xylanase supplements fed to broiler chickens. Bedford et al (1992) reported that xylanase supplementation did not improve the rate of gain, feed intake, or starch and protein digestibility in swine.…”
Section: -mentioning
confidence: 57%
“…The growth performance for birds supplemented with xylanase suggests that the level of inclusion used within this study was not beneficial. Pettersson et al (1990) observed similar lack of growth response associated with xylanase supplements fed to broiler chickens. Bedford et al (1992) reported that xylanase supplementation did not improve the rate of gain, feed intake, or starch and protein digestibility in swine.…”
Section: -mentioning
confidence: 57%
“…Enzyme supplementation greatly reduced this problem, probably attributable to the reduction of intestinal fluid viscosity (White et al, 1981) and more effective absorption of nutrients from the small intestine (Hesselman and Aman, 1986;Pettersson and Aman, 1989). Other workers have noted a considerable reduction in sticky droppings with j8-glucanase addition (Rotter et al, 19896;Pettersson et al, 1990;Brufau et al, 1991). With the wheat diet enzyme addition improved food efficiency and reduced food intake, probably because of its pentosanase activity, but had no effect on the already low percentage of sticky droppings.…”
Section: Discussionmentioning
confidence: 93%
“…The use of exogenous enzymes to reduce the feed cost represents, undoubtedly, a more versatile alternative to improve the rentability of this sector. The addition of exogenous enzymes, including b-xylosidases to diets has significant potential to improve nutritive values of feed and animal performance (Pettersson et al 1990;Beauchemin et al 2003;Omogbenigun et al 2004). Xylanolytic enzymes are capable to hydrolyze the hemicellulose present in wheat, corn and other cereals, promoting the nutrient digestibility and reducing the manure, nitrogen and phosphorus excretion.…”
Section: Biotechnological Applicationsmentioning
confidence: 99%